2006
DOI: 10.1007/s10815-006-9049-x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine vascularization and pregnancy outcome in patients undergoing intracytoplasmatic sperm injection: The role of nitric oxide

Abstract: A Doppler analysis done on day 1 of controlled ovarian hyperstimulation may be an useful indicator of ART outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Methods to preserve fertility are now available in many centers, but reduced uterine volume and inappropriate uterine blood supply in these patients have been linked to poor outcomes even during assisted reproduction therapies (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Methods to preserve fertility are now available in many centers, but reduced uterine volume and inappropriate uterine blood supply in these patients have been linked to poor outcomes even during assisted reproduction therapies (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Among other molecules, FF contains free radicals, like NO, which is actively synthesized by the granulosa cells (Lee et al, 2000). This means that NO and/or its by-products may be potential biomarkers for IVF outcome, and several studies tested this hypothesis in patients undergoing fertility treatment (Barroso et al, 1999;Barrionuevo et al, 2000;Lee et al, 2000;Battaglia et al, 2006;Vignini et al, 2008;Zhao et al, 2010;Goud et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, evidence suggests that NO levels in the follicular fluid (FF) are inversely associated with the fertilization of mature oocytes and the ability of the subsequent embryo to cleave normally (Barrionuevo et al, 2000). Furthermore, a negative correlation between FF NO levels and embryo morphology was identified (Barroso et al, 1999;Battaglia et al, 2006). On the other hand, other studies found no differences in relation to oocyte and embryo quality (Lee et al, 2000;Yalçınkaya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-based diagnostics have been in use since the 1940s. Whereas conventional ultrasound can visualize two-dimensional (2D) sections, modern three-dimensional (3D) ultrasound can provide additional information such as volume and orthogonal plane metrics ( 1 ). Doppler ultrasonographic methods measure the change in ultrasound pulse when it is reflected by an object having some velocity in the beam’s direction ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transvaginal Doppler ultrasonography has advanced the pathophysiological understanding of blood flow dynamics in the female pelvis ( 7 ). It is a useful method of examining the blood flow through the uterus, ovaries, and even in the follicles ( 1 ). Transvaginal Doppler ultrasonography has become an important component of assisted reproduction procedures.…”
Section: Introductionmentioning
confidence: 99%